Зимо- і морозостійкість північноамериканських видів глоду (Crataegus L.) в умовах дендропарку “Олександрія” - Rubis, V.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
The analysis of the winter hardiness of 12 species of North America hawthorn in the different regions of the introduction and in the conditions of the dendrological park Alexandria are given. The winter hardiness and the period of the deep dormancy of this species have been stated. The resistance against winter and spring frosts of the species are evoluted.